Flexible Two-Stage Designs: An Overview - Bauer, P.; Brannath, W.; Posch, M. (Methods of Information in Medicine, 2001)
In this overview we introduce the basic ideas behind a new flexible approach in sequential designs. The different concepts based on two-stage combination tests and conditional error functions are brought together. We sketch the construction of p-values, confidence intervals, and median unbiased estimates. Finally, recursive combination tests are introduced which extend the flexibility to the choice of the number of interim analyses.
Keywords: Adaptive Design; Midtrial Design Modification; Two-stage Combination Test; Conditional Error Function; Confidence Interval; Recursive Combination Test